Research of quality indicators of a bar made from biologically activated grain of wheat - Бажай-Жежерун, Світлана Андріївна; Антонюк, Марія Миколаївна (Technology audit and production reserves, 2015)
The parameters of biological activation of wheat brains are proposed and grounded. Experimental studies showed that the content of water-soluble vitamins and vitamin E in wheat brains increases significantly in the process of such activation. The formulation of a grain bar is developed and samples of this bar are examined in laboratory. Correlation of basic components and energy value of a grain bar is estimated. Daily intake of minerals from 100 g of grain bar is calculated. Indices of a grain bar microbiological stability during storage under the different conditions are defined. It is found that the use of plant extracts from horseradish root and a fennel seeds is efficient in sprouting to inhibit growth of microorganisms. Period of storage of biologically activated grain bar under hermetic conditions at 5 degrees °C increases to 10 days.